Altered spontaneous brain activity in children with deprivation amblyopia: a resting-state functional magnetic resonance imaging study - Yadong Li; Guangying Zheng; Baohong Wen; Xiaopan Zhang (European Journal of Medical Research)
Abstract Background To investigate the alterations in spontaneous brain activity and the similarities and differences between monocular deprivation amblyopia and binocular deprivation amblyopia. Methods Twenty children with binocular deprivation amblyopia, 26 children with monocular deprivation amblyopia and 20 healthy controls underwent resting-state functional magnetic resonance imaging. The evaluation of altered spontaneous brain activity was conducted using fractional amplitude of low-frequency fluctuations (fALFF). One-way analysis of variance was employed to analyze fALFF values among the three groups. Additionally, the relationship between fALFF values and best corrected visual acuity (BCVA) was analyzed via correlation analysis. Results Compared to healthy controls, children with binocular deprivation amblyopia presented increased fALFF values in the left medial superior frontal gyrus, left middle frontal gyrus, left anterior cingulate cortex, left postcentral gyrus and bilateral precentral gyrus, and decreased fALFF values in the right fusiform gyrus. Compared to healthy controls, children with monocular deprivation amblyopia presented increased fALFF values in the right lingual gyrus, right superior frontal gyrus, right middle frontal gyrus, left superior temporal gyrus, triangular part of the left inferior frontal gyrus and bilateral middle temporal gyrus, and decreased fALFF values in the right precuneus. Compared with monocular deprivation amblyopia, fALFF values of binocular deprivation amblyopia were decreased in the triangular part of the left inferior frontal gyrus, right lingual gyrus and right cuneus, and increased in the left precentral gyrus and left postcentral gyrus. No significant correlations were found between the fALFF values of identified regions and the BCVA of amblyopic eyes for either type of amblyopia. Conclusions Children with deprivation amblyopia presented alterations in spontaneous activity in multiple brain regions, and these alterations differed between monocular amblyopia and binocular amblyopia. These abnormal spontaneous activities may reflect dysfunctions and compensation related to amblyopia.